Reluctant reception : refugees, migration and governance in the Middle East and North Africa - Norman, Kelsey P. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"Sama is a 45-year-old woman from Syria who fled to Egypt in 2012 with her husband, her elderly mother-in-law, and her six children. They live together in a two-bedroom flat on the outskirts of Alexandria in a beach community that is populated by Egyptians during the summer, but relatively empty throughout the rest of the year"--
Includes index.
Keywords: Refugees -- Egypt; Refugees -- Morocco; Refugees -- Turkey; Immigrants -- Egypt; Immigrants -- Morocco; Immigrants -- Turkey